Connectivity-Guaranteed Hybrid Topology Management Scheme for Improving the Operational Lifetime of 3-Dimensional Wireless Sensor Networks - A. Jawahar; S. Radha; S. Vadivelan (International Journal of Distributed Sensor Networks)
The battery of limited energy operates wireless sensor nodes, it is important to increase the lifetime of the wireless sensor network. The aim of our work is to design a hybrid topology management scheme for improving the lifetime of the wireless sensor networks with guaranteed connectivity. The sensing range of the sensor node is smaller than the radio range and hence there is a large number of nodes within the coverage area of a node. Hence the network connectivity can be maintained with less number of nodes. By using this fact, we can save energy by switching off the transceiver, which consumes most of the energy. On the other hand, the sensor node spends most of the time in monitoring state and the transceiver is idle. In the idle state the transceiver consumes almost the same energy as in receiving state. Hence putting the transceiver in the sleep mode when it is idle can save the significant energy. We have designed a hybrid topology management scheme for 3-Dimensional sensor networks by making use of these facts. Our hybrid scheme improves the lifetime of the 3-Dimensional sensor network by a factor of 19.